2016
DOI: 10.1038/onc.2016.280
|View full text |Cite
|
Sign up to set email alerts
|

CSN6 controls the proliferation and metastasis of glioblastoma by CHIP-mediated degradation of EGFR

Abstract: CSN6, a critical subunit of the constitutive photomorphogenesis 9 (COP9) signalosome (CSN), has received attention as a regulator of the degradation of cancer-related proteins such as p53, c-myc and c-Jun, through the ubiquitin-proteasome system, suggesting its importance in cancerogenesis. However, the biological functions and molecular mechanisms of CSN6 in glioblastoma (GBM) remain poorly understood. Here, we report that GBM tumors overexpressed CSN6 compared with normal brain tissues and that CSN6 promoted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 33 publications
6
84
0
Order By: Relevance
“…CSN6, another subunit of COP9 family, exhibits similar structures as CSN5 and also interact by the MPN domain 22 . Overexpression of CSN6 in GBM has been shown to be associated with tumor progression 23 . CSN6 contributed to Myc stability through the CSN‐Cullin‐Fbxw7 axis during tumorigenesis in breast and pancreatic cancers 24 .…”
Section: Introductionmentioning
confidence: 99%
“…CSN6, another subunit of COP9 family, exhibits similar structures as CSN5 and also interact by the MPN domain 22 . Overexpression of CSN6 in GBM has been shown to be associated with tumor progression 23 . CSN6 contributed to Myc stability through the CSN‐Cullin‐Fbxw7 axis during tumorigenesis in breast and pancreatic cancers 24 .…”
Section: Introductionmentioning
confidence: 99%
“…We found that CSN6 greatly affected the protein expression of cyclin D, CDK4 and p16 ( Figure 3A ). Previous studies have found that the expression of CDK4 and cyclin D was reduced in the CSN6-knockdown cells 19 . It is well known that the p16 and p21 proteins are cyclin-dependent kinase inhibitors.…”
Section: Resultsmentioning
confidence: 83%
“…The CSN mediates a variety of cellular functions through its association with cullin-containing ubiquitin E3 ligases 11,16 . Previous studies have suggested that CSN6 associates with aberrant gene regulators such as MEK kinase 1 (MEKK1), E6-associated protein (E6AP) and epidermal growth factor receptor (EGFR) by facilitating ubiquitin-mediated degradation 17-19 . Moreover, CSN6 stabilizes COP1 through reducing COP1 self-ubiquitination and the CSN6-COP1 axis function as an E3 ubiquitin ligase involved in 14-3-3σ degradation to regulate cell growth and tumorigenicity 10,20 .…”
Section: Introductionmentioning
confidence: 99%
“…These data indicated that CSN6 is involved in AR intracellular trafficking. Moreover, it was previously reported that CSN6 interacts with Erk, to down regulate the EGFR signaling pathway [15]. The activation of this pathway is critical for the release of the sperm from Sertoli cells, and for blood-testis barrier integrity [20].…”
Section: Discussionmentioning
confidence: 99%
“…CSN6 reportedly controls the proliferation and metastasis of glioblastoma by chromatin immunoprecipitation-mediated degradation of epidermal growth factor receptor (EGFR) [15], extracellular regulated protein kinases (Erk)1/2-dependent phosphorylation of CSN6 is critical in colorectal cancer development [16]. We examined whether CSN6 is involved in Fig.…”
Section: Csn6 Knockdown Down-regulate Phosphorylation Signaling Pathwaymentioning
confidence: 99%